Enhancing Early Childhood Mathematics Learning through Interactive Educational Technology: A Case Study of Digital Batik - Budiarti, Erna (CV. Bimbingan Belajar Assyfa, 2025)
To improve mathematics competence in Early Childhood Education (PAUD), using interactive media based on digital technology can be an innovative solution. This study uses interactive applications that combine the art of batik painting with basic mathematical concepts. This approach is based on the theory of Contextual Learning, which is designed to introduce children to the concepts of measurement, patterns, and geometric shapes through creative activities. The prototype of this application was tested on three PAUD groups with a total of 90 children and 6 educators. The research method used qualitative descriptive analysis to assess learning effectiveness and children’s involvement in the activity. The results showed an increase in basic mathematical understanding of up to 35%, with higher enthusiasm and active participation during learning. However, the challenges faced include limited access to digital devices and the need for educators to be trained to utilize this technology. To overcome these obstacles, it is recommended that adequate digital infrastructure support and regular training programs for teachers be provided. Collaboration between schools, technology developers, and the government is needed to ensure effective integration into the PAUD curriculum. Through a collaborative approach, technology-based interactive media can make mathematics learning more interesting and compelling for early childhood.